(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Leadership Behavior can be learnt and result in leaders being formed and evolving. Leadership teaches oneself to be able to inspire and motivate others. Practicing what you preach is what a leader should follow because they inspire others to act while simultaneously directing to confirm academic success through process, material and training improvement. Usually it works better when collaborated with different perspectives from educators, parents, students, public policy makers, and the public. Leadership is highly associated with school performance and is helpful to improve classroom teaching. Leadership of school head teachers has a basic role in school because it determines the success or failure of any school. The study of leadership in schools is closely tied to the analysis of school effectiveness. The importance of leadership is reflected in every aspect of the school specially school effectiveness. Teachers who are supported by head teachers display a better sense of responsibility than those who do not have their head teachers‟ support. Head teachers can show their arts and skills in schools and it depends on how much they have created a positive and relax atmosphere for their staff and students. The focus of this paper is to find the level of leadership of school principals. In this study survey method has been employed and a self-constructed and validated Leadership Behavior Scale is used as tool for data collection. The findings of the study showed that there is no significant difference in the leadership of school principal on the basis of Gender, Education qualification and medium. However significant difference was seen with respect to the length of experience in services